Collagenase injections for Dupuytren disease: 3-year treatment outcomes and predictors of recurrence in 89 hands. (2nd November 2019) - Nordenskjöld, Jesper; Lauritzson, Anna; Åkesson, Anna; Atroshi, Isam
Abstract : Background and purpose — Few prospective studies have reported the long-term effect durability of collagenase injections for Dupuytren disease. We assessed the 3-year treatment outcome of collagenase injections and predictors of recurrence. Patients and methods — We conducted a single-center prospective cohort study. Indication for collagenase injection was palpable Dupuytren's cord and active extension deficit (AED) ≥ 20° in the metacarpophalangeal (MCP) and/or proximal interphalangeal (PIP) joint. From November 2012 through June 2013, we treated 86 consecutive patients (92 hands, 126 fingers). A hand therapist measured joint contracture before, 5 weeks, and 3 years after injection. The patients rated their treatment satisfaction. Primary outcome was proportion of treated joints with ≥ 20° AED worsening between the 5-week and 3-year measurements. We analyzed predictors of recurrence. Results — 3-year outcomes were available for 83 of the 86 patients (89 hands, 120 treated fingers). Between the 5-week and 3-year measurements, AED worsened by ≥ 20° in 17 MCP (14%) and 28 PIP (23%) joints. At 3 years, complete correction (passive extension deficit 0–5°) was present in 73% of MCP and 35% of PIP joints. Treatment of small finger PIP joint contracture, greater pretreatment contracture severity, and previous fasciectomy on the treated finger were statistically significant predictors of recurrence. Treatment satisfaction was rated as very satisfied or satisfied in 59 of 87 hands. No long-term treatment-related adverse events were observed. Interpretation — 3 years after collagenase injections for Dupuytren disease, improvement was maintained and treatment satisfaction reported in two-thirds of the treated hands, with no adverse events. Complete contracture correction was achieved in 3 of 4 MCP joints, but in only a third of the PIP joints.